2018
DOI: 10.3389/fnagi.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Association Between MicroRNAs Polymorphisms and Risk of Ischemic Stroke: A Meta-Analysis in Chinese Individuals

Abstract: Objective: Previous studies have demonstrated that some single-nucleotide polymorphisms (SNPs) in miRNAs are related to the risk of ischemic stroke (IS), but the conclusions are still controversial and inconclusive. We performed this meta-analysis to further assess the association between miR-146a C>G (rs2910164), miR-149 T>C (rs2292832), miR-196a2 T>C (rs11614913), miR-499 A>G (rs3746444) and risk of IS in Chinese individuals.Methods: Relevant studies were identified in the databases of PubMed, Embase. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Patients P1 and P3 presented the rs3746444 variant in hsa-miR-499a/b, resulting in an altered expression profile with common phenotypic features of RASopathies, congenital cardiomyopathy, and pulmonary stenosis. These data corroborate the results found in other studies that have suggested cardiovascular diseases are associated with this miRNA variant (Fawzy et al, 2018; Li et al, 2018). The miRNA hsa-miR-499 has previously been associated with the development and functioning of the heart, showing high expression in cardiac tissue, and with alterations in physiological and pathological processes during myocardial injury and remodelling (Dorn et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Patients P1 and P3 presented the rs3746444 variant in hsa-miR-499a/b, resulting in an altered expression profile with common phenotypic features of RASopathies, congenital cardiomyopathy, and pulmonary stenosis. These data corroborate the results found in other studies that have suggested cardiovascular diseases are associated with this miRNA variant (Fawzy et al, 2018; Li et al, 2018). The miRNA hsa-miR-499 has previously been associated with the development and functioning of the heart, showing high expression in cardiac tissue, and with alterations in physiological and pathological processes during myocardial injury and remodelling (Dorn et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, Li et al22 reported that the level of miRNA 146a was significantly lower in ischemic stroke patients in the acute phase, compared to patients in the subacute phase and healthy controls. Such findings were further supported by genetic studies which demonstrated a significant association between miRNA 146a polymorphisms and the risk of ischemic stroke23,24; however, this association is still debatable 25…”
Section: Discussionmentioning
confidence: 77%
“…Firstly, it disturbs miR-499 regulation of blood pressure; secondly, it hampers miR-499 anti-apoptotic effect in cardiomyocytes [105]. In a recent study by Li et al, it has been reported that the G allele of the rs3746444 is associated with ischemic stroke in the Chinese population [115]. Li et al, suggested that the association of rs3746444 with ischemic stroke because miR-499 has roles in the reduction of the activation of the mitochondrial fission program mediated by Drp1 [115], as well as it has roles in the regulation of expression of inflammatory cytokines such as C-reactive protein and interleukins [115].…”
Section: Mir-499 Rs3746444 A>gmentioning
confidence: 99%